2016
DOI: 10.1016/j.jdsr.2016.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of diagnostic imaging for the assessment of pain symptoms in temporomandibular disorders

Abstract: SummaryThe causes of pain symptoms in the temporomandibular joint (TMJ) and masticatory muscle (MM) regions may not be determined by clinical examination alone. In this review, we document that pain symptoms of the TMJ and MM regions in patients with temporomandibular disorders (TMDs) are associated with computed tomography and magnetic resonance (MR) findings of internal derangement, joint effusion, osteoarthritis, and bone marrow edema. However, it is emphasized that these imaging findings must not be regard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(26 citation statements)
references
References 155 publications
(215 reference statements)
0
23
0
3
Order By: Relevance
“…These abnormalities are considered to be radiological signs of osteoarthrosis and are frequently observed in joints with long-standing anterior disc displacement without reduction. 17 Emshoff et al 11 showed that significant increases in risk of pain occurred with 'disc displacement without reduction and osteoarthrosis', 'disc displacement without reduction and absence of osteoarthrosis', and 'disc displacement with reduction and osteoarthrosis'. Furthermore, Emshoff et al 12 suggest that TMJ pain is related to internal derangement, osteoarthrosis, effusion and bone marrow oedema.…”
Section: Discussionmentioning
confidence: 99%
“…These abnormalities are considered to be radiological signs of osteoarthrosis and are frequently observed in joints with long-standing anterior disc displacement without reduction. 17 Emshoff et al 11 showed that significant increases in risk of pain occurred with 'disc displacement without reduction and osteoarthrosis', 'disc displacement without reduction and absence of osteoarthrosis', and 'disc displacement with reduction and osteoarthrosis'. Furthermore, Emshoff et al 12 suggest that TMJ pain is related to internal derangement, osteoarthrosis, effusion and bone marrow oedema.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that the key treatment for the pains that involve the various joints of the body, including TMJ, is to reduce the overload and allow joint movement as soon as possible ( 1 - 3 , 9 , 10 ). Dystrophic calcification / medullar sclerosis seen on magnetic resonance imaging, when present in TMJ indicates an advanced stage of arthropathy ( 11 , 12 ), but sometimes representing little pain or signs typical of temporomandibular disorders ( 13 ), probably due to increased joint space and decompression caused by the alteration of the anatomical form of the condyle, fossa and joint eminence.Regarding the displacement of the TMJ joint disc, it has been suggested that the disc repositioning is conditioned by the increase of the joint space with mandibular orthopedic modification called joint decompression ( 2 , 3 ), and the increase of space is the main responsible for joint disc maintenance. Thus, the long-term stability of the disc tissues is conditioned to the increase of the joint space, consequently the rehydration and increase of volume of the tissues, as well as the need to occupy the increased space between the jaws connected to the resting caused by the deprogramming, that’s why the IO / interocclusal orthotic is used.…”
Section: Discussionmentioning
confidence: 99%
“…Computed tomography (CT) and magnetic resonance (MRI) are widely useful tools for imaging the TMJ region of TMD patients, in particular for assessing degenerative bony changes, disc position and configuration, inflammatory pathological changes in the posterior disc attachment, the presence of effusion in joint spaces, and bone marrow edematous involvement [43]. Cone beam computed tomography (CBCT) allows the visualization of the TMJ in all three planes with high resolution, minimal distortion, and great precision for identifying condylar cortical changes [44].…”
Section: Tmj-oa: Imagenological Characteristicsmentioning
confidence: 99%